Organizer of International Conference on Science and Applied Science (Engineering and Educational Science) 2016 - - - (International Journal of Science and Applied Science: Conference Series, 2017)
OrganizerGraduate Program, Physics Department, Sebelas Maret University, Indonesia Jl. Ir. Sutami 36A Kentingan Jebres Surakarta 57126, IndonesiaPhone/fax : 0271-669017 psw 308Email       : icsas@mail.uns.ac.idChairmanProf. Suparmi, M.Sc., Ph.D, Sebelas Maret University, Indonesia Dr. Fuad Anwar, S.Si.,M.Si, Sebelas Maret University, IndonesiaOrganizing CommitteeProf. Cari, M.A., M.Sc., PhD, Sebelas Maret University, IndonesiaAhmad Marzuki, S.Si., Ph.D., Sebelas Maret University, IndonesiaDr. Eng Budi Purnama, S.Si, M.Si., Sebelas Maret University, IndonesiaDr. Fahru Nurosyid, S.Si.M.Si., Sebelas Maret University, IndonesiaDrs. Harjana, M.Si. M.Sc., Ph.D, Sebelas Maret University, IndonesiaDr. Agus Supriyanto, S.Si,M.Si. Sebelas Maret University, IndonesiaDr. Yofentina Iriani, S.Si.,M.Si., Sebelas Maret University, IndonesiaDr.Eng. Risa Suryana, S.Si,M.Si., Sebelas Maret University, IndonesiaKhairuddin, S.Si.,M.Phil, Ph.D., Sebelas Maret University, IndonesiaDrs. Iwan Yahya, M.Si., Sebelas Maret University, IndonesiaMohtar Yunianto, S.Si,M.Si., Sebelas Maret University, IndonesiaNuryani,S.Si,M.Si, Ph.D., Sebelas Maret University, Indonesia